Species distribution of coagulase-positive staphylococci in animals. - Biberstein, E L (1984)
A total of 268 isolates of coagulase-positive staphylococci from a variety of animal species, including dogs, horses, cats, monkeys, goats, and cows, were assigned to species on the basis of the API Staph- Ident system (Analytab Products, Inc., Plainview , N.Y.). Of 195 isolates from dogs, 179 (91.8%) were Staphylococcus intermedius, as were 9 of 25 (36%) isolates from horses, 7 of 15 (46.6%) isolates from cats, and 4 of 6 (66.6%) isolates from goats. Only 1 of 10 isolates from monkeys and none of 7 isolates from cows were S. intermedius. Of the remaining 68 cultures, 63 were identified as Staphylococcus aureus and 5 as Staphylococcus hyicus. The latter identifications were rendered doubtful on the basis of conventional tests. Identification appeared to be more certain in the S. aureus sample than in the S. intermedius sample. Distribution of biotypes within the two bacterial species as represented by different API profile numbers and reactivity on test substrates showed no significant variations among the host species, except for the S. aureus biotypes in dogs. Both Staphylococcus species were represented about equally among samples from different tissues and lesions, apart from skin-related infections in dogs, which were associated exclusively with S. intermedius (P less than 0.01). Differences between S. aureus and S. intermedius in antimicrobial susceptibility patterns, prevalence of clumping factor, and occurrence of beta-toxin were found to be not significant.